Analisis Tingkat Kepuasan Mahasiswa Pengguna E-learning Berbasis Moodle Pada ITB STIKOM Bali - I Gusti Ayu Desi Saryanti (STMIK Banjarbaru, 2023)
Moodle-based e-learning is one of the software that can be used for teaching and learning purposes with the principles of social construction pedagogy. The End User Computing Satisfaction method of an information system is an overall evaluation of the users of the information system based on their experience in using the system. Evaluation using this model emphasizes end-user satisfaction with the technology aspect, with the content, accuracy, format, time and ease of use of the system. With the change in the e-learning model used by students, it became the background of this research which was carried out so that it would know the level of student satisfaction as a moodle-based e-learning user by using the End User Computing Satisfaction method. Based on the results of calculations carried out, the values generated by each indicator are Content = 33.64 (84.1) %. Format = 3.25 (81.2) %, Accuracy = 3.31 (82.8) %, Timeliness = 3.28 (82.1) %, and Easy of Use = 3.25 (81.3) %.Keywords: End User Computing Satisfaction; E-Learning; Satisfaction level; Moodle AbstrakE-learning berbasis Moodle merupakan salah satu software yang dapat digunakan untuk keperluan belajar mengajar dengan prinsip social construction pedagogy. Metode End User Computing Satisfaction dari sebuah sistem informasi adalah evaluasi secara keseluruhan dari para pengguna sistem informasi yang berdasarkan pengalaman mereka dalam menggunakan sistem tersebut. Evaluasi dengan menggunakan model ini lebih menekankan kepuasan (satisfaction) pengguna akhir terhadap aspek teknologi, dengan isi, keakuratan, format, waktu dan kemudahan penggunaan dari sistem. Dengan adanya perubahan model e-learning yang dipergunakan oleh mahasisawa melatar belakangi penelitian ini dilakukan sehingga akan mengetahui tingkat kepuasan mahasiswa sebagai pengguna e-learning berbasis Moodle dengan menggunakan metode End User Computing Satisfaction. Berdasarkan hasil perhitungan yang dilakukan nilai yang dihasilkan oleh masing-masing indikator yaitu Content = 33.64 (84.1) %, Format = 3.25 (81.2) %, Accuracy = 3.31 (82.8) %, Timeliness = 3.28 (82.1) %, dan Easy of Use = 3.25 (81.3) %